A Review of Safety Issues among Small Grade Contractors in Construction Industry - Noorhayatie, Yusof; Mohd Saidin, Misnan (EDP Sciences, 2019)
The construction industry is one of the largest industries in Malaysia. There were too many factors that contribute to construction project success. Construction industry comprises different participants including clients, consultants, and contractors (as construction business) that perform different roles from conception in order to complete the project. The contractors in Malaysia were categorized into seven Grades of contractors starting from contractor G1 to G7. These categories were graded based on a number of employees and the value of the project. In Malaysia, G1 to G4 contractors (small grade contractors) are the highest company were registered with the Construction Industry Development Board (CIDB). Unfortunately, small grade contractors are widely exposed to the highest rate of accidents or risky compared to medium and large grade contractors (G5-G7) in this industry. In order to adequately clarify the issues on this safety matter, this paper has discussed the problems faced by small grade contractors that influence the implementation of safety practice in a construction site. The objective of study is to identify the problems in small grade contractors in order to implement safety practice on site. This study was focused on small grade contractor in Malaysia. The data for this study were supported by previous studies are reported in the journal; statistic of accidents in the construction industry by Department of Occupational Safety and Health (DOSH); contractor information; statistic of contractors are registered under CIDB; safety book; and internet sources. This study had found that the small grade contractors have some issues related to safety practice whereas they did not have proper standard of safety (general safety act and regulation); they cannot appoint Safety Health Officer (SHO) to handle the site safety; have limited external resource; and also small grade contractors have financial constraints. Based on this review, it can be concluded that small grade contractors have more lacking in safety management and consequently, the rate of accidents still higher in the construction industry. However, safety management in small grade contractors can be improved with support by external resources such as researcher, large grade contractor, government, and pressure from authorities.